2018
DOI: 10.1001/jama.2018.6537
|View full text |Cite
|
Sign up to set email alerts
|

Screening to Prevent Osteoporotic Fractures

Abstract: In women, screening to prevent osteoporotic fractures may reduce hip fractures, and treatment reduced the risk of vertebral and nonvertebral fractures; there was not consistent evidence of treatment harms. The accuracy of bone measurement tests or clinical risk assessments for identifying osteoporosis or predicting fractures varied from very poor to good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 114 publications
0
134
1
2
Order By: Relevance
“…None of these are validated AI-treated women with breast cancer. One of the strongest risk factors for AI-induced fractures is having osteopenia or osteoporosis at the time of starting AI [ 65 ]. The development of FRAX ® uses clinical risk factors (i.e., age, height, weight, sex, prior personal history of fracture, parental history of hip fracture, current smoking, glucocorticoids, secondary osteoporosis, alcohol greater than three drinks/day), with or without femoral neck BMD to estimate to the ten-year risks of a hip or non-hip fracture [ 66 ].…”
Section: Determining Fracture Riskmentioning
confidence: 99%
“…None of these are validated AI-treated women with breast cancer. One of the strongest risk factors for AI-induced fractures is having osteopenia or osteoporosis at the time of starting AI [ 65 ]. The development of FRAX ® uses clinical risk factors (i.e., age, height, weight, sex, prior personal history of fracture, parental history of hip fracture, current smoking, glucocorticoids, secondary osteoporosis, alcohol greater than three drinks/day), with or without femoral neck BMD to estimate to the ten-year risks of a hip or non-hip fracture [ 66 ].…”
Section: Determining Fracture Riskmentioning
confidence: 99%
“…Firstly, the high level of genetic predisposition to OP, muscle status and OF: the heritability of BMD was estimated between 60% and 90% [ 616 , 617 , 618 ], the heritability of OFs was estimated between 9.5% [ 619 ] to 16–35% [ 620 , 621 , 622 ] and 53–70% [ 617 , 623 , 624 ] and the heritability of muscle-related traits was estimated between 30% and 50% [ 625 , 626 , 627 ]. Secondly, only in half of patients (between 30% and 50%) antiresorptive drugs are effective [ 628 , 629 , 630 , 631 , 632 ]. Thirdly, among lifestyle preventive measures, only muscle strengthening, balance and posture exercises are beneficial (level of evidence A), whereas reduced smoking (level of evidence C) and alcohol consumption (level of evidence D) demonstrate low relevance [ 633 , 634 ].…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Within the field of osteoporosis, one potential answer lies with the FRAX tool itself. Many studies have examined its clinical utility since its launch in 2008; two systematic reviews have demonstrated the significant predictive ability of FRAX for future fractures, especially of the hip [ 22 , 23 ]. In general, the incorporation of a measurement of femoral neck BMD results in higher accuracy than without BMD, but the additional value of BMD in all is modest [ 24 ].…”
Section: Discussionmentioning
confidence: 99%